Econometrics for dummies - Pedace, Roberto (Hoboken, NJ : John Wiley & Sons Inc, 2013)
Econometrics can prove challenging for many students unfamiliar with the terms and concepts discussed in a typical econometrics course. Pedace eliminates that confusion with easy-to-understand explanations of important topics, and provides you with an easy-to-follow course supplement to further refine your understanding of how econometrics works and how it can be applied in real-world situations.
Introduction -- Getting started with econometrics -- Building the classical linear regression model -- Working with the classical regression model -- Violations of classical regression model assumptions -- Discrete and restricted dependent variables in econometrics -- Extending the basic econometric model -- The part of ten -- Appendix: Statistical tables.
Includes index.
Keywords: Econometrics